Pendidikan agama Islam dalam pemberdayaan masyarakat anak usia dini - ALIFAH (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2023)
The purpose of this research is to analyse how the influence of Islamic religious education on community empowerment in early childhood in madrasah diniyah AL-HUDA and TPQ Al-abdullah in Tlogosari sub-district Bondowoso district. Islamic religious education has an important role in empowering the early childhood community because at their age it is considered fast enough to receive information and become the most valuable time for them. The research method used is a qualitative method with data collection techniques through interviews and observations. Research results show that Islamic religious education can have a positive impact on the empowerment of the early childhood community, especially in increasing religious awareness, developing good character, and increasing participation in community activities. Therefore, efforts need to be made to improve the quality of Islamic religious education and expand its access for early childhood. Students who study well will become more insightful so that they understand what they should do and what not to do. The implication of this research is to help early childhood make it easier to learn Islam so that they can become ethical and knowledgeable Muslims and they can do good deeds in society because they are the successors of the nation whose goodness is expected